(untitled) - Boulton, Chris (Oxford, 2001)
This unique volume provides a definitive overview of modern and traditional brewing fermentation. Written by two experts with unrivalled experience from years with a leading international brewer, coverage includes all aspects of brewing fermentation together with the biochemistry, physiology and genetics of brewers' yeast
Keywords: Yeast.,Brewing.,Fermentation